The world's great men of music - Brower, Harriette (AUK lassics ;, 2010)
This excellent ebook introduces the reader to a wide range of the world's greatest composers, including interesting facts about not only their musical styles but the men themselves. This edition has been specially formatted for today's e-readers, and will appeal to all those looking for a fascinating read about the history of classical music.